Studies on Photocatalytic Degradation of Methylene Blue Using TiO2—Transition Metal Oxides Heterojunctions - Maria Grapin; Valentin Raditoiu; Alina Raditoiu; Florentina Monica Raduly (Proceedings)
One of the sources of water pollution is the wastewater generated from the textile industry [...]